Towards a better learning models through OCWs and MOOCs - Cordero, Alicia; Jordán, Cristina; Sanabria-Codesal, E.; Torregrosa, Juan Ramón (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
echnological advances of XXth century have induced a profound change in society and, therefore, in the high education. Internet supposed a qualitative difference, as information and digital images flooded into homes around the world. The Universitat Politècnica de València (UPV) is a medium sized university of Spain that has been involved in the development of digital video content (Polimedia) to support teaching processes for several years. Joint with Polimedia and other learning objects (virtual laboratories, applets, etc.), the UPV promoted the construction of OCWs. Along with the improvement of technology, MOOCs appeared as e-learning material. In this work, we analyze the advantages and drawbacks of OCWs and MOOCs when they are used in our classroom. This experience has led us to incorporate in our methodology the flip teaching.
Keywords: learning objects; video surveillance; digital economy; MOOCs; IJIMAI